Raft foundations with settlement reducing piles-performance and design considerations - Chang, Ming Fang (2008)
The objectives of this study are to investigate (1) the behavior of conventional rafts and rafts with settlement reducing piles, including the effect of consolidation, (2) the interaction between the raft, the settlement reducing piles and the base soil, and (3) alternative approaches to the design of settlement reducing piles.